Efficacy of Cortexin and Methylprednisolone on Traumatic Facial Nerve Paralysis - Tunccan, Tuncay; Yalcin, Sinasi; Demir, Caner Feyzi; Akin, Mehmet Mustafa; Karlidag, Turgut; Keles, Erol; Kaygusuz, Irfan (Aves, 2016)
OBJECTIVE: The aim was to investigate the efficacy of cortexin and methylprednisolone on recovery in cases of traumatic facial nerve paralysis occurring after facial nerve trauma. MATERIALS and METHODS: The study was performed on 21 healthy rabbits. The buccal branches of the left facial nerves of all the rabbits were pressed, and facial nerve paralysis occurred. The rabbits were randomly divided into three equal groups: 3 mg/day cortexin intramuscularly, 1 mg/kg/day methylprednisolone intramuscularly, and 3 mg/day saline intramuscularly were administered for 10 days in Group I (cortexin group), Group II (methylprednisolone group), and Group III (control group), respectively. Electromyography was performed on the 7th, 14th, and 21st days to evaluate their improvement. Following this, the traumatic buccal branches of the facial nerves of rabbits were extracted and subjected to histopathological examination. RESULTS: There was a significant difference between the cortexin and methylprednisolone groups and the control group in terms of neural fibrotic degeneration, myelin degeneration, axonal degeneration, normal myelin production, and edema. When the cortexin and methylprednisolone groups were compared with each other, there was no significant difference between them, except for an increase in collagen fibers. Cortexin significantly reduced the collagen fiber increase to a greater extent than methylprednisolone. The electromyography findings did not show any significant difference between the groups or within the groups. CONCLUSION: Our study suggests that cortexin and methylprednisolone are effective for healing traumatic facial nerve paralysis with intact nerve integrity; however, cortexin is unable to cause significant improvement, which is superior to that caused by methylprednisolone.
Keywords: Facial nerve paralysis; cortexin; methylprednisolone; electromyography